AUXILIARY TROOPS IN THE FLORENTINE ARMED FORCES IN THE XIII - XIV CENTURIES - V. V. Timchenko (Гуманитарные и юридические исследования, 2021)
The article analyses the typical features of Florentine military organization in the XIII - XIV-th centuries. The author focuses on the auxiliary formations such as Communal colour guardians and «moving men» squardons, as well as their social status, organization and equipment.